The Effect of Financial Literacy and Financial Behavior on the Performance of MSMEs on Madura Island - Haryadi, Bambang; Angraini, Merie Satya; Hamat, Zahri; Latifah, Lyna (Journal of International Conference Proceedings, 2023)
This study aims to find empirical evidence on the influence of financial literacy and financial behavior on the development of MSME financial performance. The research approach used is quantitative, and is located on Madura Island. The population in this study includes all MSMEs on Madura Island. While the samples taken amounted to 62 MSME samples covering four districts. By using the multiple regression analysis method, the results showed that: (1) The financial literacy variable has a significant influence on the performance of MSMEs. (2) The financial behavior variable does not have a positive influence on the performance of MSMEs.